An evaluation of the CAPS refugee doctor scheme in London – a survey of outcomes. Issue 2 (4th March 2021) - Shah, Rupal; Moodambail, Abdul; Alam, Mohammed; Ragiwala, Deena; Mulamehic, Fahira
ABSTRACT: The NHS faces challenges in recruiting and retaining clinicians. The NHS Long-Term Plan aims to increase NHS staffing levels as one of its objectives. With adequate support, refugee doctors can help fill gaps in staffing and deliver high-quality patient care. There is a moral imperative to support this group: to promote inclusion and equality. London is the only region in England to offer refugee doctors the opportunity of a funded six-month supernumerary F2 role with access to a bespoke education programme and to the resources offered by the Professional Support Unit (PSU). Our aim was to evaluate retention rates of refugee doctors in the NHS following this six-month placement. Between October 2009 (at the inception of CAPS) to March 2020, 85 refugee doctors entered the CAPS programme. Of the 48 doctors who responded to our questionnaire, 45 are still working in the NHS (93.8%). Most are working as Locally Employed Doctors across a range of hospital specialities (47%) but general practice was the single most popular career choice (29%). The CAPS scheme is successful in integrating refugee doctors into the NHS at a relatively low cost. More support should be offered to this group in terms of career progression, and the scheme should be rolled out to other regions of the UK, particularly those in which there is a shortage of doctors.